ANALISIS STRATEGI CITRA MEREK DALAM MENINGKATKAN KEPUASAN PELANGGAN OCTO MOBILE - Oktaviani Oktaviani; Zulkifli Zulkifli; Edi Supriadi (Universitas Muhammadiyah Metro, 2021)
The purpose of this study was to determine the effect of promotion, service quality, and innovation directly or indirectly on Brand Image, as well as the effect of all these variables on OCTO Mobile customer satisfaction. The research sample was 385 respondents who were CIMB Niaga customers. The sampling technique was purposive sampling—data collection using a questionnaire and FGD. The data analysis technique used Structural Equation Modeling (SEM) analysis which aided with SmartPLS software. The study results prove that the variables of service quality and innovation have a significant effect on brand image and brand image has no significant effect on customer satisfaction. However, the promotion variable does not have a significant effect on brand image. Promotion variables, service quality, and innovation significantly affect customer satisfaction, while the brand image variable has no significant effect on customer satisfaction. The results also show the customer satisfaction strategy plan by referring to the strategies from the analysis that has been done, and the right strategy is selected, namely product development.